2004
DOI: 10.1017/s0033291703001065
|View full text |Cite
|
Sign up to set email alerts
|

A pragmatic cluster randomized controlled trial of an educational intervention for GPs in the assessment and management of depression

Abstract: Background. General practitioners (GPs) can be provided with effective training in the skills to manage depression. However, it remains uncertain whether such training achieves health gain for their patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 24 publications
2
62
0
Order By: Relevance
“…Passive educational interventions have been shown to be ineffective, however, 43 and more-interactive educational initiatives involving patients as teachers should be considered. 44 Learning relationship-centered consultation skills 44 during both their undergraduate and postgraduate training is essential for family physicians.…”
Section: Training Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Passive educational interventions have been shown to be ineffective, however, 43 and more-interactive educational initiatives involving patients as teachers should be considered. 44 Learning relationship-centered consultation skills 44 during both their undergraduate and postgraduate training is essential for family physicians.…”
Section: Training Issuesmentioning
confidence: 99%
“…Passive educational interventions have been shown to be ineffective, however, 43 and more-interactive educational initiatives involving patients as teachers should be considered. 44 Learning relationship-centered consultation skills 44 during both their undergraduate and postgraduate training is essential for family physicians.In addition, patient initiatives, such as the Expert Patient Programme, 45 may help to reduce the disparity between family physicians and patients; indeed, it has been shown that the Expert Patient Programme might reinforce the medical paradigm. …”
mentioning
confidence: 99%
“…Two articles (Moreno et al, 2003;Scott et al, 2002) found improved identification of depression in patients. On the other hand, two further interventions (Gask et al, 2004;Scott et al, 2002) resulted in significant improvements in only one out of two different locations. Finally, the remaining two interventions (Kick, 1999;Thompson et al, 2000) did not result in any significant effects.…”
Section: General Remarksmentioning
confidence: 98%
“…Although Gask et al (2004) did not describe a needs assessment as such, the results still allow for relevant interpretation. As discussed above, this intervention had a significant effect in Manchester but not in Liverpool, whilst on baseline measurements participating GPs in Liverpool had greater previous experience in psychiatry and training in counselling skills.…”
Section: Needs Assessments Reasoning For Using Needs Assessmentsmentioning
confidence: 99%
“…8,13 Even following identification, many young people with psychological disorders receive no specific management or follow-up, 8 perhaps because health professionals hesitate to address issues when they lack confidence in their own skills, or in the treatments available. 14 An authoritative statement that (in this age group) symptoms of depression are common and often resolve without psychological or medical intervention may have influenced practitioners. 15 While there has been considerable emphasis on training GPs to identify and manage adult psychiatric disorders, little work has addressed psychopathology in…”
Section: Introductionmentioning
confidence: 99%